Development and preclinical studies of 64Cu-NOTA-pertuzumab F(ab′)2 for imaging changes in tumor HER2 expression associated with response to trastuzumab by PET/CT. Issue 1 (2nd January 2017) - Lam, Karen; Chan, Conrad; Reilly, Raymond M.
ABSTRACT: We previously reported that microSPECT/CT imaging with 111 In-labeled pertuzumab detected decreased HER2 expression in human breast cancer (BC) xenografts in athymic mice associated with response to treatment with trastuzumab (Herceptin). Our aim was to extend these results to PET/CT by constructing F(ab′)2 of pertuzumab modified with NOTA chelators for complexing 64 Cu. The effect of the administered mass (5–200 µg) of 64 Cu-NOTA-pertuzumab F(ab′)2 was studied in NOD/SCID mice engrafted with HER2-positive SK-OV-3 human ovarian cancer xenografts. Biodistribution studies were performed in non-tumor bearing Balb/c mice to predict radiation doses to normal organs in humans. Serial PET/CT imaging was conducted on mice engrafted with HER2-positive and trastuzumab-sensitive BT-474 or trastuzumab-insensitive SK-OV-3 xenografted mice treated with weekly doses of trastuzumab. There were no significant effects of the administered mass of 64 Cu-NOTA-pertuzumab F(ab′)2 on tumor or normal tissue uptake. The predicted total body dose in humans was 0.015 mSv/MBq, a 3.3-fold reduction compared to 111 In-labeled pertuzumab. MicroPET/CT images revealed specific tumor uptake of 64 Cu-NOTA-pertuzumab F(ab′)2 at 24 or 48 h post-injection in mice with SK-OV-3 tumors. Image analysis of mice treated with trastuzumab showed 2-fold reduced uptake of 64 Cu-NOTA-pertuzumab F(ab′)2 in BT-474 tumors after 1 week of trastuzumab normalized to baseline, and 1.9-fold increased uptake in SK-OV-3 tumors after 3 weeks of trastuzumab, consistent with tumor response and resistance, respectively. We conclude that PET/CT imaging with 64 Cu-NOTA-pertuzumab F(ab′)2 detected changes in HER2 expression in response to trastuzumab while delivering a lower total body radiation dose compared to 111 In-labeled pertuzumab.